La política eclesiástica de Urbano V en la diócesis de León: las súplicas beneficiales - Díaz Ibáñez, Jorge (Estudios humanísticos. Geografía, historia y arte, 2001)
In this article, based on unpublished documentation coming from the Vatican Registers, there is an analysis about the requests for ecclesiastical benefices which were presented to pope Urbanus V (1362-1370) referring to the diocese of Leon, in the Kingdom of Castille. The concern for these request lies in the information which they supply about the sociopolitic relations and clientèle networks related to the Leonese clergy, as far as most of the clergymen who obtain benefices are relatives and protégés of important persons, such as king Pedro I, princess Beatriz or cardinals Guillermus and Aegidius de Albornoz. Finally, it must be remarked that most of the requests are benefices in the Leonese cathedral chapter, because they provided a greater income.